Peran Wisata Kampung Budaya Karawang Berbasis Local Wisdom Terhadap Ketahanan Sosial Budaya - Rusmiyati, Sri; Rahmatiani, Lusiana; Nugraha, Yogi (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
ABSTRACT The era of increasing globalization has had various impact on the existence of indigenous regional culture, local wisdom values, one of which is the degradation of the feeling of love for one’s homeland and the increasingly fading feeling of love for the pride of Indonesian culture which is one's identity. a nation, especially for young people. This research aims to determine the role of the Karawang Cultural Village Tourism which is located at Jl. Wadas Cultural Village, East Telukjambe District, Karawang Regency, West Java. with tourismBased on Local Wisdom towards Socio-Cultural Resilience. This research uses data collection techniques using observation, interviews and documentation. Data analysis techniques to find results are carried out by collecting data, reducing, presenting data, and drawing conclusions/verification. The results of this research are that the Karawang Cultural Village Tourism has great potential in maintaining and preserving traditions in maintaining socio-cultural resilience, however there are several obstacles that need to be overcome to ensure its sustainability and effectiveness. The research identifies and analyzes the obstacles faced by Karawang Cultural Village tourism which is based on local wisdom.